2019
DOI: 10.1016/j.compstruct.2019.111493
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of composite plates based on a variable separation method

Abstract: This work deals with the free vibration analysis of laminated composite plates through a variable separation approach. The displacement field is approximated as a sum of separated functions of the in-plane coordinates x y , and the transverse coordinate z. This choice yields to a non-linear problem that can be solved by an iterative process. That consists of solving a 2D and 1D eigenvalue problem successively. In the thickness direction, a fourth-order expansion in each layer is considered. For the in-plane de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…That is why the natural frequency increases as number of layers increases and consequently the natural frequency decreases as aspect ratio increases. The effect of aspect ratio (a/b) on natural frequency for cross ply clamped boundary condition as shown in Figure (11). It is observed that as increasing the aspect ratio, the natural frequency of two layers decreases about 45% less than of four layers.…”
Section: Resultsmentioning
confidence: 95%
“…That is why the natural frequency increases as number of layers increases and consequently the natural frequency decreases as aspect ratio increases. The effect of aspect ratio (a/b) on natural frequency for cross ply clamped boundary condition as shown in Figure (11). It is observed that as increasing the aspect ratio, the natural frequency of two layers decreases about 45% less than of four layers.…”
Section: Resultsmentioning
confidence: 95%
“…reference. It should be mentioned here that for the cantilever and the clamped beam tests it is required to build simutaneously 2-tuple in order to achieve accurate results as in [54]. Further information on this technique can be also found in [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…43 (b), that when the thickness ratio increases, it leads to a reduction in plate stiffness, which causes lower FV frequency values. Moreover, Vidal et al [364] employed the variable separation method (VSM) to investigate the FV of LCPs, and the FEM has been used for the in-plane description. Furthermore, Fantuzzi et al [365] performed a simulation analysis on LCPs with various geometries by utilizing the linear approach of moderately thick plates, and the strong form of FEM as well as WFm was used for solving the problem.…”
Section: Tablementioning
confidence: 99%